SISTEM OTOMATISASI RENDERING VIDEO TEMPLATE AFTER EFFECTS BERBASIS WEB DENGAN EXTENDSCRIPT DAN FLASK - Ragil Raditya Saputra; Zacky Innova; Epsilona Katiga Capricorna; Bambang Irawan; Ridwan Ramadhan; Muhammad Hafizh Rahman Hakim (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
The process of creating animations or videos in Adobe After Effects typically requires repetitive and time-consuming manual interaction, making it less efficient in digital multimedia workflows. To address this challenge, this study designed a web-based rendering automation system by integrating ExtendScript, After Effects' internal scripting language, and the Flask framework as the backend. The HTML-based interface allows users to input parameters such as text, color, or formatting options, which are then processed by Flask and passed to After Effects via a local subprocess. Beyond integration, we also compared this automation system with manual methods. This system increased work efficiency by up to 67.78% compared to traditional manual methods and supported automated processing based on user input. This system provides a practical and affordable solution for users who want to accelerate the production of visual content from After Effects templates with customizations to text and color, without compromising the flexibility and quality of the final result. This technology integration demonstrates that automating the creative process can be done effectively, stably, and easily accessible via the web if further developed.